Diamond film growth by microwave plasma enhanced chemical vapour deposition - Tan, Fong Hock. (2009)
Diamond particles and continuous films have been successfully grown by Microwave Plasma Enhanced Chemical Vapour Deposition (MPECVD). The particles and films were characterised using scanning electron microscopy (SEM), atomic force microscopy (AFM) and Raman spectroscopy. Current-Voltage measurement and secondary ions mass spectrometry were being used to verify the presence of boron in the boron-doped diamond film. Silicon (Si) is mainly used as a substrate for the experimental studies.